Budget Control Mechanism in Budgeting Function PT XYZ - Muhammad Zaidan; Reni Yendrawati (Dinasti International Journal of Digital Business Management, 2026)
Budget control plays a strategic role in ensuring cost effectiveness and operational sustainability, particularly in state-owned enterprises operating within a holding company structure. PT. XYZ, as part of the Integrated Marine Logistics Subholding under PSI, faces high operational complexity and diverse cost structures that require effective budget control mechanisms. This study analyzes the implementation of budget control within the Budgeting Function of PT XYZ and its contribution to effective cost management. This research employs a descriptive qualitative approach. Data were collected through direct observation of budget control activities, informal interviews with Budgeting Function staff, and documentation reviews, including the Company Work Plan and Budget (RKAP), standard operating procedures, and budget realization reports. Data analysis was conducted descriptively by examining workflows, control mechanisms, and factors influencing the effectiveness of budget control implementation. The results indicate that budget control at PT. XYZ has been systematically implemented with strong emphasis on pre-transaction control. The verification and authorization process of Purchase Requisitions (PR) through the MySAP system, including a double-release mechanism, ensures budget availability, compliance with approved allocations, and organizational authority. The effectiveness of budget control is influenced by cost center clarity and budget classification into Operational Expenditure